Safety and performance of oropharyngeal muscle strength training in the treatment of post-stroke dysphagia during oral feeding: protocol for a systematic review and meta-analysis - Xin Wang; Ying Wang; Fenghua Zhou; Minxing Gao; Lingyuan Xu; Heying Wang; Jinan Song; Xiaoqiu Yang (BMJ Open)
Introduction Dysphagia is a common functional disorder after stroke. Most patients post-stroke are incapable of oral feeding, which often leads to complications such as malnutrition, aspiration pneumonia and dehydration that seriously affect the quality of life of patients. Oropharyngeal muscle strength training is a major method of swallowing training, and recent studies have focused on healthy adults, elderly persons, and patients with head and neck cancer or neurodegenerative diseases; but there have been few studies on such training in patients with post-stroke dysphagia. Our study aims to systematically review the safety and performance of oropharyngeal muscle strength training in the treatment of post-stroke dysphagia during oral feeding.Methods and analysis The Cochrane Library, Web of Science, PubMed, Embase and ClinicalTrials.gov databases will be systematically searched, and all relevant articles in English from the establishment of the databases to January 2022 will be reviewed. The study will be conducted in accordance with the recommendations of the Cochrane Handbook for Systematic Reviews of Interventions and will be reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta Analyses guidelines. The primary outcome measures include the Penetration–Aspiration Scale and the Functional Oral Intake Scale. Two authors will independently screen the articles, extract the data and assess the study quality. Any disagreements during this process will be resolved by discussion or by consultation with a third author. Next, quantitative or qualitative, subgroup and sensitivity analyses of the included literature data will be performed as appropriate.Ethics and dissemination Ethical approval is not required for this systematic review as no primary data collection will be required. The results of the present study will be published in a peer-reviewed journal in the field of deglutition disorders.PROSPERO registration number CRD42022302471.